Intellectual Capital Disclosure dan Kinerja Keuangan: Systematic Literature Review - Fadiyah, Nur Laily; Sabillah, Natasya; Islamiyah, Maya Adillah; Fernanda, Erfina; Hermawan, Sigit (Journal of Culture Accounting and Auditing, 2023)
This research aims to find out the direction of development of Intellectual Capital Disclosure and Financial Performance research for 7 years (2015-2022) by mapping or classifying according to themes and according to keywords. By using a literature review system as the basis for research analysis, this research uses a descriptive qualitative approach to collect data. The articles reviewed were taken from Sinta indexed or accredited Sinta-2 journal sources. The research results show: (1) Mapping according to theme shows that the Sinta 2 Accredited Scientific Journal with the name "Accounting or Accounting" totals 10 journals; (2) Mapping according to keywords shows that the number of articles with the keywords Intellectual Capital Disclosure and Financial Performance is 16 articles. The researchers emphasized many limitations of this article. The author determined this limitation by only looking at articles published in the accredited journal Sinta 2 and focusing on the study of Intellectual Capital Disclosure and Financial Performance in Indonesia. Articles from other countries were not included in the review. As a result, there may be articles on certain subjects that are not covered in this review. Although the limitations of this article are the results of the review that the author described, it cannot be concluded that it can generally be applied in Indonesia due to the limited scope of much research